Relationship of HIV status and fatigue, cardiorespiratory fitness, myokines and physical activity - Webel, Allison R. (J Assoc Nurses AIDS Care, 2019)
People living with HIV (PLHIV) experience high rates of fatigue which can be improved with physical activity. We examined the relationship between HIV infection, fatigue, cardiorespiratory fitness, physical activity, and myokines. Twenty HIV-positive and 20 HIV-uninfected adults completed an assessment of fatigue, a maximal cardiometabolic exercise test (VO(2) peak, VE/VO(2,) VO(2) at anaerobic threshold), serum measures of myokines (Il-15, IL-7, FGF-21, adiponectin), and wore an accelerometer for seven days. Measures were completed at baseline, 3 and 6 months. At baseline, PLHIV had more fatigue (4.7 ±2.6 vs 2.8 ±2.5, p=0.01) and higher peak VE/VCO(2) (33 ±5.5 vs. 30.2 ±2.5, p=0.06). Fifty percent of PLHIV engaged in at least one 10-minute bout of physical activity in the past week, compared to 65% of the control group. Over time, HIV infection and FGF-21 were associated with fatigue (p<0.05). PLHIV have more fatigue and a higher ventilator efficiency and expression of FGF-21 may be a mechanism underpinning this relationship.